A multi-targeted In Silico approach to select and rank regenerative drugs for managing diabetic wound inflammation signalling through IGFR, TNFR and PPAR -γ pathways - Priyadarsini S Lakshmi; L Sreelakshmi; S Saritha A.; Prakash Gopika (BIO Web of Conferences)
The present research work explores the possibilities of molecular docking to predict and rank the most suitable drugs for diabetic foot ulcer or any degenerate inflammatory wounds among ten different drugs commonly used in wound regeneration. This is achieved by targeting multiple pathways simultaneously in inflammation and wound healing, Tumour necrosis factor Receptor pathway (TNFR) and Peroxisome Proliferator-Activated Receptor -γ (PPAR-γ) for macrophage polarization, inflammation management, collagen deposition etc., and Insulin-like Growth Factor Receptor (IGFR) signalling for wound regeneration. Molecular docking studies were carried out using Swiss Dock which ranked the natural Phyto estrogenic isoflavone Genistein as the best having strong binding affinity to all the receptors TNFR, PPAR-γ, and IGFR; highlighting its potential to regulate inflammation, macrophage polarization, pro angiogenic properties and thus wound regeneration.